Pathogenesis of Streptococcus agalactiae in hybrid tilapia, Oreochromis niloticus (Linnaeus, 1758) x Oreochromis mossambicus (Peter, 1852) - Pang, Sing Tung (Terengganu: Universiti Malaysia Terengganu, 2014)
This study was conducted to examine the development of Streptococcosis in farmed tilapia (Oreochromis sp.). The fish samples were collected from WakafTapai, Kuala Terengganu. The fish samples were screened and acclimatized to the water condition in Freshwater Hatchery of Universiti Malaysia Terengganu for two weeks before the experiment been conducted.